Modified High-Protein Diet and Their Impact on Sarcopenia and Prognosis in Breast Cancer Patients: A Scoping Review - Sujiati Kurnia, Eva; Hofifa Sevira Wulandari; Inggita Kusumastuty; Kanthi P. Tritisari; Fuadiyah Nila Kurniasari; Fajar Ari Nugroho (Indonesian Journal of Human Nutrition, 2025)
Breast cancer rank as the second most frequently diagnosed cancer worldwide and remains the leading cause of cancer-related deaths among women, with high incidence rates, including in Indonesia. A prevalent complication is sarcopenia, characterized by decreased muscular strength and volume, which increases the possibility of postoperative complications, reduces therapy response, lowers overall health status, and elevates the risk of death. One potential strategy to counter sarcopenia is increasing protein intake through dietary modification. This scoping review aimed to evaluate the impact of a diet rich in protein on sarcopenia progression and the prognosis of breast malignancy patients, using a Scoping Review approach. Literature was sourced from PubMed and Oxford Academic databases from 2014 to 2024 with specific keyword combinations: “Breast Cancer” OR “Breast Neoplasm” with “High Protein Diet” AND “Sarcopenia” OR “Sarcopenias” AND “Prognosis” OR “Prognoses”, then filtered using inclusion and exclusion criteria. Analysis of 12 selected studies shows that increased dietary protein intake (≥2-2.5 g/kg body weight/day) positively affects breast cancer patients with sarcopenia. Sarcopenia worsens prognosis by increasing mortality risk and therapy toxicity: however, higher protein intake, especially when combined with physical activity, improves muscle mass and function. The modified high-protein diet is essential in managing breast cancer, particularly for those at risk of or experiencing sarcopenia. Further research is needed to reinforce current findings and determine optimal dietary strategies for this patient group.